“Analisis Manajemen Persuteraan Bombyx Morry L Di Sukabumi Jabar Dan Pelajaran Untuk Menunjang Perancangan Program PUSK Attacus atlas Belitang OKUT”: Silkworm Farming Management of Bombyx mori L in Sukabumi and Its Implications for the Development Plan of Attacus atlas in East OKU Regency - Aisyah; Mubarok, Husni (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2025)
The plan for community silkworm cultivation activities, especially wild silkworms (Attacus atlas) in the East OKU region in partnership with the Central Lembur Cultural Village must be carried out by manipulating the room in terms of shape, walls, and roof so that it can meet the standards for silkworm habitats with a maximum temperature of 28-30 0C. The availability of silkworm feed can be done by utilizing yard land so that land utilization occurs. Farmers should also have skills in weaving so that they can sell finished products in the form of cloth to increase income. This study examines the rules of the game and the method of cocoon production agreed upon and implemented by farmers in the Central Lembur Cultural Village, Sukabumi Regency and calculates the income level of partner silkworm farmers in the Central Lembur Cultural Village. With a qualitative approach, this study discusses the organization, cooperation patterns, project preparation, project mechanisms and cooperation agreements. The results show that a partnership is established that supports and complements each other both in terms of management and technical implementation of silkworm cultivation. The prospect of developing silkworms (Attacus atlas) in Beliatng can be implemented by looking at the potential for existing feed and utilizing the local community's yard land.